SMART calls for SOS - Husna, Hashim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
2 June 2010. Sekolah Menengah Abdul Rahman Talib (SMART) Kuantan students were enlightened with a talk on Study Orientation Skills (SOS) delivered by Mohd Ghani Awang who is a CMLHS Senior lecturer from the Department of Human Sciences. It is from his extensive research that he created the Ghani Format (Format Ghani). Hence, the main objective of the talk was to discuss and utilise Ghani Format in science subjects to the fourth formers of the school. There were 120 students of science stream and 30 teachers took part in the process.